2015
DOI: 10.4155/tde.14.108
|View full text |Cite
|
Sign up to set email alerts
|

‘Close-to-ideal’ Tumor Boron Targeting for Boron Neutron Capture Therapy is Possible With ‘less-than-ideal’ Boron Carriers Approved for Use in Humans

Abstract: Keywords: boron compounds approved for use in humans • boron neutron capture therapy (BNCT) • BPA • GB-10 • optimization of boron tumor targeting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The considered BSH concentrations were equivalent to 40 ppm (parts per million) and 80 ppm of 11 B. These were chosen based on values from the literature on the 10 B-enriched BSH analogue used in BNCT in order to achieve the optimal intracellular 10 B concentration 35,46,47 . In particular, similar boron-equivalent concentration ranges of another BNCT compound, BPA, had been previously used with the same cell line in vitro 48 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The considered BSH concentrations were equivalent to 40 ppm (parts per million) and 80 ppm of 11 B. These were chosen based on values from the literature on the 10 B-enriched BSH analogue used in BNCT in order to achieve the optimal intracellular 10 B concentration 35,46,47 . In particular, similar boron-equivalent concentration ranges of another BNCT compound, BPA, had been previously used with the same cell line in vitro 48 .…”
Section: Resultsmentioning
confidence: 99%
“…The rationale underlying BNCT consists in cancer irradiation by thermal neutrons, which results in a highly localized and mostly lethal targeting of cancer cells because of the very short range and, hence, of the high LET of the low-energy alpha particles generated in the reaction with the 10 B atoms. However, despite numerous, carefully designed and generally promising clinical trials 53,54 , BNCT struggles to establish itself in clinical routine, both because of the intrinsically challenging quest for ideal carriers to deliver radiobiologically effective concentrations of boron to cancer cells, and because of the limited availability of thermal neutron sources 35,47 . On the other hand, albeit already being a clinical reality, external beam 12 C-ion hadrontherapy, which is capable of delivering very biologically effective radiation doses with extremely high precision to the tumor target, is hampered by economic and radiobiological issues as discussed in the Introduction section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings concerning a selective 'phylogenetic' or 'cellular' toxicity of BCCs have suggested their usefulness for treating infectious diseases or some types of cancer (Park, 2004;Di Fiore, 2010;Scorei, 2011c;Scorei, 2013b;Nielsen, 2014;Schwint, 2015). In this sense, some BCCs have notable antimicrobial activity on some pathogenic species, and some molecular targets have been identified on these microorganisms (proteasomes, penicillin binding proteins, carbonic anhydrases, synthetases, etc.).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 97%
“…It has been suggested that BCCs exert greater toxicological effects on neoplastic than healthy cells, mainly due to their use in metabolism (Beardsley, 2003;Calabrese, 2012;Roda, 2014Schwint, 2015. In fact, BCCs have shown effects on breast, colorectal and prostate cancer (Park, 2004;Di Fiore, 2010;Scorei, 2011c;Scorei, 2013b).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 98%